Fretting damage of high carbon chromium bearing steel - Kuno, Masato (1988)
This thesis consists of four sections, the fretting wear properties of high carbon chromium bearing steel; the effect of debris during fretting wear; an introduction of a new fretting wear test apparatus used in this study; and the effects of fretting damage parameters on rolling bearings.